Nursing First Aid to Emergency Events in Agricultural Areas: Literature Review - Enggal Hadi Kurniyawan; Titik Sandiva Yustiana; Putri Shofiyyah Firdaus; Salsabhila Nasywa Ramadhanti; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (KHD Production, 2023)
Being a farmer who works directly in the environment certainly has many risks at work, one of which is the occurrence of unwanted events that can threaten the health of farmers. Some problems are classified as emergencies and must be handled immediately to avoid fatalities. One example is the occurrence of snake bite emergencies in farmers. This study aims to determine some emergencies in agricultural areas and how to provide first aid. The method used in this study was a literature review of articles from article search engines such as PubMed, Google Scholar, and Science Direct analyzed using the PRISMA technique by including articles published in the last five years. The results found that emergencies that often occur in agricultural areas include venomous snake bites, pesticide poisoning, contracting dengue fever from mosquitoes, and rat bites that cause rat-bite fever. First aid methods that can be performed on someone whom a snake has bitten are by calming the victim, immobilizing the victim's entire body by laying him in the recovery position and immobilizing the affected body part using either a sling, splint, or pressure bandage immobilization (PBI) method. Nurses have a role in educating and counseling farmers on how to first aid someone who experiences snake bites, rat bites that cause rat bite fever, and drowning in fishermen.